The Concept of Islamic Economic Fiqh in Mu’amalah Perspective - Efendi, Faisal; Candra, Afrikal; Mardianton, Mardianton; Fauzi, M.; Ilham, Elgi Muhammad; Sumarni, Ira (Samara: Journal of Islamic Law and Family Studies, 2023)
Islamic Economic Fiqh is an important foundation for understanding and applying economic principles in Islam, with a special focus on muamalah or daily life transactions. This discussion aims to find out the concept of Islamic economic jurisprudence from several experts and also aims to find out what is the scope of the discussion of Islamic economic jurisprudence (Fiqh Iqtishad). Islamic economic jurisprudence is knowledge about activities or transactions based on Sharia law and about human behavior in their lives obtained from detailed Islamic postulates. The scope of Islamic economic jurisprudence is all human economic activities based on Islamic law in the form of regulations containing commands or prohibitions such as obligatory, sunnah, haram, makruh, and permissible. In general, the scope of Islamic economics includes economic aspects, including Syirkah and mudharabah, murabahah, khiyar, istisna, ijarah, salam, kafalah, hawalah, and others. However, the aspect of cooperation that is most often carried out is profit sharing, namely Syirkah, and mudharabah. Fiqh law consists of legal laws regarding matters of worship about the vertical relationship between humans and Rabb and human relationships with other humans.